Analisis Gaya Kepemimpinan Terhadap Kinerja di CV Damai - Sheva Dhaifullah Sheehan; Putri Mahabbatun Aliyah; Erlangga Aditya Pratama; Hajmi Ahmad Padila (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the leadership style applied by the leader of CV Damai, its role in human resource management, and its influence on employee performance. The research uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews, participatory observation, documentation, and literature review. The informants consisted of the owner of CV Damai and employees who are directly involved in the company’s daily operational activities. The findings indicate that the leadership style implemented at CV Damai tends to reflect a transformational leadership style. This is shown through the leader’s active involvement in providing direction, motivation, and building open and communicative working relationships with employees. The leader plays a significant role in managing human resources by directly supervising, guiding, and motivating employees, as well as providing appreciation for good performance and corrective feedback when work standards are not met. The application of transformational leadership has a positive impact on employee performance, particularly in improving work motivation, responsibility, discipline, and the quality of work results. However, the study also identifies challenges in leadership implementation, especially related to differences in age and experience between the relatively young leader and senior employees, which may affect consistency in decision-making. Overall, transformational leadership at CV Damai is considered effective and has the potential to further enhance employee performance when applied consistently and adaptively.